Pendampingan Digitalisasi UMKM Pasar Lama Kota Serang: Menuju Pasar yang Lebih Luas melalui Digitalisasi dan E- Commerce - Ismarina Ismarina; Dini Rahmah; Dewi Anggraini (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
Pasar Lama in Serang City is one of the traditional MSME centers with competitive local products; however, most business actors still rely on conventional systems without digital marketing strategies. This condition is reflected in low digital literacy, limited use of marketplaces and social media, and the absence of collective branding efforts. This community service program aimed to improve digital literacy, strengthen business management, and expand market access through the digitalization of MSMEs in the Pasar Lama area. The methods applied included program socialization, training on digital financial management, cost of goods sold (COGS) calculation, product branding, digital marketing, e-commerce activation, and participatory-based mentoring. The results demonstrated significant progress: 18 MSMEs have created marketplace accounts, 15 MSMEs are actively using business social media, and 20 MSMEs have implemented simple digital financial recording. In addition, product branding quality improved, and participants were actively involved in forming a digital mentoring group within the market community. In conclusion, this program successfully facilitated the transformation of traditional MSMEs into a digitally oriented business ecosystem, although more intensive mentoring is required to ensure program sustainability.